The Effect Dose and Soaking Time of Camellia sinensis Solution to the Egg Adhesion and Hatching of Pangasionodon hypophthalmus - Baihaki, Aldi; Nur Asiah; Nuraini, Nuraini (Jurnal Akuakultur Indonesia, 2024)
Cultivation of Pangasianodon hypophthalmus is growing rapidly, but there was a problem with the egg’s adhesiveness. Overcome this problem given a tea solution that serves as a remove of Pangasianodon hypophthalmus egg adhesion. This study conducted on June 2022 at Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, University of Riau. The purpose of this study was determining the effect of immersion eggs with different doses and immersion duration of the black tea (Camellia sinensis) solution on adhesion of Pangasianodon hypophthalmus eggs. This study used a Completely Randomized Design Factorial with 2 factors. The first factor was the dose (g/L) of the black tea with 4 levels; 0 (D0), 8 (D8), 10 (D10), and 12 (D12). The second factor was the immersion duration (minutes) with three levels of 3 (W3), 4 (W4), and 5 (W5). Pangasianodon hypophthalmus larvae reared for 7 days. Parameters measured were egg adhesion, fertilization rate, hatching rate, survival rate, and water quality. The result showed that the doses of C. sinensis solution had a significant effect (P<0.05) on the degree of fertilization and hatching of Pangasianodon hypophthalmus eggs. The optimum treatment with a dose of 10 g/L and 4 minutes (D10W4) give increased eggs adhesion 5.99%, fertilization rate 94.13%, hatching rate 92.88%, and survival rate 96.99%. The water quality during the study were temperature 26.7-27.9OC, pH of larvae maintenance water 6.5-7.1 and DO 4.0-5.2 mg/L. There is an interaction between dose and immersion duration of C. sinensis solution to the egg adhesion and hatching eggs of Pangasianodon hypophthalmus.